Arctigenin suppresses transforming growth factor-β1-induced expression of monocyte chemoattractant protein-1 and the subsequent epithelial–mesenchymal transition through reactive oxygen species-dependent ERK/NF-κB signaling pathway in renal tubular epithelial cells. (September 2015) - Li, A.; Wang, J.; Zhu, D.; Zhang, X.; Pan, R.; Wang, R.
Abstract Transforming growth factor-β1 (TGF-β1) induces expression of the proinflammatory and profibrotic cytokine monocyte chemoattractant protein-1 (MCP-1) in tubular epithelial cells (TECs) and thereby contributes to the tubular epithelial–mesenchymal transition (EMT), which in turn leads to the progression of tubulointerstitial inflammation into tubulointerstitial fibrosis. Exactly how TGF-β1 causes MCP-1 overexpression and subsequent EMT is not well understood. Using human tubular epithelial cultures, we found that TGF-β1 upregulated the expression of reduced nicotinamide adenine dinucleotide phosphate oxidases 2 and 4 and their regulatory subunits, inducing the production of reactive oxygen species. These reactive species activated a signaling pathway mediated by extracellular signal-regulated kinase (ERK1/2) and nuclear factor-κB (NF-κB), which upregulated expression of MCP-1. Incubating cultures with TGF-β1 was sufficient to induce hallmarks of EMT, such as downregulation of epithelial marker proteins (E-cadherin and zonula occludens-1), induction of mesenchymal marker proteins (α-smooth muscle actin, fibronectin, and vimentin), and elevated cell migration and invasion in an EMT-like manner. Overexpressing MCP-1 in cells exposed to TGF-β1 exacerbated these EMT-like changes. Pretreating cells with the antioxidant and anti-inflammatory compound arctigenin (ATG) protected them against these TGF-β1-induced EMT-like changes; the compound worked by inhibiting the ROS/ERK1/2/NF-κB pathway to decrease MCP-1 upregulation. These findings suggest ATG as a new therapeutic candidate to inhibit or even reverse tubular EMT-like changes during progression to tubulointerstitial fibrosis, and they provide the first clues to how ATG may work.